2007
DOI: 10.1073/pnas.0707678104
|View full text |Cite
|
Sign up to set email alerts
|

Short-term meditation training improves attention and self-regulation

Abstract: Recent studies suggest that months to years of intensive and systematic meditation training can improve attention. However, the lengthy training required has made it difficult to use random assignment of participants to conditions to confirm these findings. This article shows that a group randomly assigned to 5 days of meditation practice with the integrative body-mind training method shows significantly better attention and control of stress than a similarly chosen control group given relaxation training. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
936
7
30

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,266 publications
(1,079 citation statements)
references
References 37 publications
60
936
7
30
Order By: Relevance
“…However, it was of course not representative for mindfulness in general. Mindfulness was closely associated with well-being (Brown et al, 2007;Kabat-Zinn, 1990;Shapiro et al, 2006;Tang et al, 2007) and represents the basis for psychotherapeutic concepts such as mindfulness based cognitive therapy for depression (MBCT, Teasdale et al, 1999) or mindfulness based stress reduction (Grossman et al, 2004), which are increasingly applied in psychotherapeutic and psychiatric practice (Allen et al, 2006). Mindfulness has been defined as a receptive attention to and awareness of present experience (Brown and Ryan, 2003).…”
Section: Emotion Introspection and Clinical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was of course not representative for mindfulness in general. Mindfulness was closely associated with well-being (Brown et al, 2007;Kabat-Zinn, 1990;Shapiro et al, 2006;Tang et al, 2007) and represents the basis for psychotherapeutic concepts such as mindfulness based cognitive therapy for depression (MBCT, Teasdale et al, 1999) or mindfulness based stress reduction (Grossman et al, 2004), which are increasingly applied in psychotherapeutic and psychiatric practice (Allen et al, 2006). Mindfulness has been defined as a receptive attention to and awareness of present experience (Brown and Ryan, 2003).…”
Section: Emotion Introspection and Clinical Implicationsmentioning
confidence: 99%
“…Training of mindfulness was reported to increase LPFC-insular connectivity during word reading (Farb et al, 2007), with complex activation modifications in expert meditators compared to novices (Brefczynski-Lewis et al, 2007). Mindfulness related meditation short-term training further lead to improved attention and self-regulation in the sense of stress control (Tang et al, 2007).…”
Section: Emotion Introspection and Clinical Implicationsmentioning
confidence: 99%
“…The latter study also observed that the meditators increased mindfulness level over an active control group (Zeidan et al, 2010). Moreover, Tang et al (2007) observed that the people who underwent a 5-day intensive mindfulness meditation retreat showed greater improvement in executive attention, better mood, and decreased stressrelated cortisol compared with a control group. Higher attentional control and cognitive flexibility in experienced meditators are correlated with higher self-reported levels of mindfulness (Moore & Malinowski, 2009).…”
Section: Introductionmentioning
confidence: 72%
“…Previous studies have suggested that long-term meditation leads to changes in brain regions important to both cognitive control and emotional regulation (Hölzel et al, 2011;Lazar et al, 2005). People who underwent a short-term meditation training reported better moods (Tang et al, 2007). Future research could disentangle the contributions of attentional and emotional regulation to the ability of mindfulness training to enhance BCI performance.…”
Section: Discussionmentioning
confidence: 95%
“…Meditation is a useful tool to achieve mindfulness and a mindful mind is an alert mind. A number of empirical studies have shown that attention increases significantly after going through a period of guided meditation practice compared to the same period of relaxation practices or compared to control groups (Kratter & Hogan, 1983;Cranson, Orme-Johnson, Gackenbach, Dillbeck, Jones & Alexander, 1991;Tang, Ma, Wang, Fan, Feng, Lu, Yu, Sui, Rothbart, Fan & Posner, 2007;Barragan, Lewis & Palacio, 2007;Rangan, Nagendra & Bhatt, 2009;MacLean, Ferrer, Aichele, Bridwell, Zanesco, Jacobs, King, Rosenberg, Sahdra, Shaver, Wallace, Mangun & Sharon, 2010). Furthermore, attention measures have proven to be significantly higher in meditation experts compared to non-meditators or novices (Davidson, Goleman & Schwartz, 1976;Sabel, 1980;Brown, Forte & Dysart, 1984;Rani & Rao, 1996;2000;Valentine & Sweet, 1999;Moore & Malinowski, 2009).…”
Section: Brief Review Of Empirical Research In Mindfulness Attentionmentioning
confidence: 99%